STRATEGI PENGADILAN AGAMA SOREANG DALAM MENGOPTIMALKAN PELAYANAN SIDANG KELILING PASCA IMPLEMENTASI INPRES NO. 1 TAHUN 2025 TENTANG EFESIENSI - Ahmad Rojak Lahabato; Aden Rosadi; Burhanuddin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to examine the implementation of Presidential Instruction No. 1 of 2025 on the allocation and realization of the mobile court budget, analyze the factors that support and hinder efficiency, and develop strategies for the Soreang Religious Court in supporting the quality of the mobile court program. This research uses an empirical juridical approach and descriptive methods, with primary data from interviews with court officials and secondary data from institutional documents and legal literature. This research found that the efficiency policy has resulted in a reduction in the frequency of mobile court sessions and a more efficient schedule. Mobile court sessions were successfully implemented due to supporting factors, including leadership commitment, information technology integration, and inter-agency synergy, while the obstacle was the lack of community participation in mobile court sessions, with people preferring to attend sessions at the court building. Cooperation with local governments and the Religious High Court has created a strategy that balances administrative efficiency and substantive justice, which is a finding of this study, particularly in court governance based on public interest.